2018
DOI: 10.1016/j.watres.2017.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Medium shapes the microbial community of water filters with implications for effluent quality

Abstract: a b s t r a c tLittle is known about the forces that determine the assembly of diverse bacterial communities inhabiting drinking water treatment filters and how this affects drinking water quality. Two contrasting ecological theories can help to understand how natural microbial communities assemble; niche theory and neutral theory, where environmental deterministic factors or stochastic factors predominate respectively. This study investigates the development of the microbial community on two common contrastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 37 publications
(56 reference statements)
7
52
0
Order By: Relevance
“…It is an often under-appreciated, complementary element of microbial ecology, which is essential for determining bacterial growth rates and substrate utilisation kinetics, for theoretical modelling (Meynet et al, 2014(Meynet et al, , 2012, mass balances (Vignola et al, 2018) and for comprehensive interpretation of microbiome surveys (Props et al, 2017). Therefore, the search for rapid and reliable techniques to estimate microbial cell numbers in diverse environments, and in filter media specifically, has become a scientific priority (Davis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is an often under-appreciated, complementary element of microbial ecology, which is essential for determining bacterial growth rates and substrate utilisation kinetics, for theoretical modelling (Meynet et al, 2014(Meynet et al, , 2012, mass balances (Vignola et al, 2018) and for comprehensive interpretation of microbiome surveys (Props et al, 2017). Therefore, the search for rapid and reliable techniques to estimate microbial cell numbers in diverse environments, and in filter media specifically, has become a scientific priority (Davis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, historical contingency, or the order in which microorganisms arrive, has been shown to play a large role in the resulting community [14,15] and has also been shown to impact interactions [16]. Both niche and neutral factors have been shown to impact microbial community assembly on sand filters [17]. Understanding the influence of selection versus neutral factors will be important for engineering the microbial community of EIS to enhance biotransformation since efforts could be thwarted if drift or dispersal drive the community away from a desired state.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and composition of the microorganisms in biosand filters have been characterized across a broad range of operating conditions. Most previous work on the microbial communities in biosand filters has focused on continuously operated systems representative of municipal-scale systems (5,8,13,(21)(22)(23)(24)(25), while only limited work focused on intermittently operated filters, typical of household-scale systems (26)(27)(28). This gap in our knowledge of the microbial communities in intermittently operated biosand filters is important given that many intermittently operated filters are implemented in conditions with less monitoring and often without posttreatment disinfection steps (2).…”
mentioning
confidence: 99%
“…Haig et al (29) showed that similar microbial communities developed in both lab-and full-scale filters continuously operated with the same source water. Other studies have highlighted the importance of filter medium type for community diversity and filter performance (21,23). These studies have found Planctomycetes, Bacteriodetes, Alphaproteobacteria, and Betaproteobacteria to be the most abundant bacterial taxa in drinking water filtration systems (8,(21)(22)(23)(24)(25)29).…”
mentioning
confidence: 99%
See 1 more Smart Citation